Temperature effect on propylene polymerization behavior over Ziegler-Natta catalyst with different cocatalyst systems - Thanyaporn Pongchan; Piyasan Praserthdam; Bunjerd Jongsomjit (Materials Research Express, 2020)
This study focused on the effect of temperature in propylene polymerization behaviors up on different cocatalysts employed. It revealed that triethylaluminum (TEA) exhibited higher activity than tri-n-octylaluminum (TnOA) with the optimal temperature of 60 °C, whereas the over reduction of catalyst occurred at 70 °C. However, at low temperature (ca. 50 °C), the mixed cocatalysts (TEA + TnOA) gave the highest activity among the sole cocatalyst. This can be attributed to the occurrence and stabilization of proper Ti oxidation state (Ti ^3+ ) form as proven by the electron spin resonance (ESR) with the combination of cocatalysts. In addition, temperatures and types of cocatalyst did not have significant effects on morphology and crystallinity of polymer.